The Role of the TIMPERSARI Teaching Aid in Enhancing Students’ Mathematical Problem-Solving Skills in One-Variable Linear Equations - Zenfiqa Aditya Ramadhani Br Sitepu; Irvan Irvan; Tua Halomoan Harahap (JMEA : Journal of Mathematics Education and Application, 2025)
This study aims to examine the role of the TIMPERSARI (Linear Equation Balance Scale) teaching aid in improving students' mathematical problem-solving abilities on the topic of One-Variable Linear Equations (PLSV). The background of the study stems from the low level of basic algebraic concept understanding and the limited use of concrete media in junior high school mathematics learning. This research employed a descriptive qualitative approach with data collection techniques including classroom observation, student worksheets, student reflections, teacher interviews, and documentation. The results indicated that the use of the TIMPERSARI tool significantly enhanced students’ conceptual understanding of equivalence, encouraged more systematic problem-solving strategies, and fostered students’ affective and collaborative engagement. Additionally, students' reflections and teacher interviews revealed positive responses to the media implementation, both in terms of conceptual understanding and learning motivation. This study concludes that TIMPERSARI is effective in bridging abstract concepts into meaningful, concrete experiences and is a viable innovative alternative in junior high school mathematics education.